Lactic acid bacteria bacteriocins as novel antimicrobials against antibiotic-resistant Streptococcus pneumoniae in opthalamic infections - Marriam Wasif; Nazish Mazhar Ali; Syed Abdullah Mazhar; Sher Muhammad Zaman; Seher kiran; Maham Chaudhry; Ibtissem Louiz; Amor Hedfi; Manel Ben Ali; Arslan Muhammad Ali Khan; Itrat Zahra (Molecular Biology Reports, 2026)

Comparative Analysis of Polymeric and Lipid Polymer Hybrid Nanoparticles: In-Vitro and In-Vivo Analysis for Pulmonary Delivery of Atorvastatin - Kifayat Ullah Shah; Muhammad Usama Ghani Khan; Fahad Y. Sabei; Muhammad Danish Saeed; Firdous Ahmad Burki; Muhammad Yasir Ghani Khan; Awaji Y. Safhi; Ahmad Salawi; Abdullah Alsalhi; Ali Hanbashi (Journal of Pharmaceutical Innovation, 2026)

Mitigation of aflatoxin B1-induced toxicopathology and immunosuppression in broilers using a multimodal antioxidant formulation - Muhammad Asad Ali; Muhammad Abdullah Arshad; Aisha Khatoon; Muhammad Kashif Saleemi; Shafia Tehseen Gul; Muhammad Umar Ijaz; Sadaf Faiz; Aneela Amin (Mycotoxin Research, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Integrative Network Pharmacology and Molecular Dynamics Simulation Uncover Key Molecular Targets of Curcumin and Its Derivatives in Colorectal Cancer - Usama Ilahi; Muhammad Suleman; Abrar Mohammad Sayaf; Muhammad Rizwan; Fazal Akbar; Zafar Ali; Haji Khan; Zahid Hussain; Mohammad Ali; Hadi M. Yassine; Abdullah A. Shaito; Sergio Crovella (Journal of Pharmaceutical Innovation, 2026)

Exploring the Molecular Mechanism of Arbutin as a Potential Inhibitor Against Melanoma: Insights from Network Pharmacology, Molecular Docking, Dynamics Simulations, and DFT Analysis - Md Rashedul Islam; Ishtiaq Qadri; Muhammad Afzal; Misbahuddin Rafeeq; Abdullah Alfaifi; Khadijah Abdullah Alfaifi; Sami I. Alzarea; Ehab M. M. Ali; Imran Kazmi (Journal of Pharmaceutical Innovation, 2026)

CRISPR-based gene editing for antimicrobial resistance control in human medicine - Abdullah Afzal Alvi; Muzzamil Hussain; Sadia Noureen; Zahid Abbas Malik; Sidra Zahoor; Areej Jamil; Muhammad Ali Mohsin; Asad Azeem; Haseeb Javaid; Zeshan Hassan (Archives of Microbiology, 2026)

Retraction notice to “Environmentally responsive and anti-bugs textile finishes – Recent trends, challenges, and future perspectives” [Sci. Total Environ. 690 (2019) 667–682] - Shahzad Ali Shahid Chatha; Muhammad Asgher; Rabbia Asgher; Abdullah Ijaz Hussain; Yasir Iqbal; Syed Makhdoom Hussain; Muhammad Bilal; Faizan Saleem; Hafiz M.N. Iqbal (Science of The Total Environment, 2026)

New horizons in treating emerging contaminants: From laboratory to real-world applications - Shakila Abdullah; Siti Amira Othman; Nur Aisyah Abdul Halim Lim; Farhad Ali; Muhammad Syafrudin (Current Opinion in Environmental Science & Health, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Spatiotemporal dynamics of historical and future drought conditions over the Arabian Peninsula from ERA5 and CMIP6 data - Muhammad Haroon Siddiqui; Mazen E Assiri; Sajjad Saeed; Md Arfan Ali; Moutassem El Rafei; Shahad Bahamdan; Abdullah Masoud Alqahtani; Abdulrahman AlHaidari; Abdulrahman Alsalhi; Ohood Alzahrani; Shamsuddin Shahid (Journal of Earth System Science, 2026)

Breaking the bloom: Exploring the genetic pathways in crop plants from primordia formation to seed development - Saba Bashir; Ali Raza; Muhammad Abdullah Bashir; Pengfei Jiang; Muhammad Ahmad Hassan (Plant Science, 2026)

Comparative evaluation of carbon sequestration and climate change mitigation in commercially planted eucalyptus-based agroforestry systems in a semi-arid region - Ghulam Yasin; Muhammad Azeem Akhter; Muhammad Zubair; Muhammad Talha Imtiaz; Matoor Mohsin Gilani; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Dilnoza Sotiboldiyeva; Shafeeq Ur Rahman (Journal of Environmental Studies and Sciences, 2026)

A comprehensive review of the phytochemical, and pharmacological potential of Alnus hirsuta (Spach) Rupr., (Siberian Alder): implications for anti-inflammatory therapeutics - Sajid Ali; Adnan Amin; Muhammad Saeed Akhtar; Khizar Abdullah Khan; Ishaq N. Khan; Imran Khan; Wajid Zaman; Atif Ali Khan Khalil (Inflammopharmacology, 2026)

Surveillance of citrus canker: a threat to Pakistani citrus industry-status and distribution of citrus canker in major citrus growing regions of Pakistan - Safi Ullah; Zia ur Rehman; Muhammad Tayyab; Aamir Iqbal; Abdullah Jalal; Jinbiao Ma; Muhammad Awais; Sajid Ali (Journal of Plant Pathology, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

Harnessing sulfide/oxide interface in NiS-CuO-g-C3N4 nanocomposite for enhanced Electrocatalytic degradation AYR mineralization in wastewater - Wishal Zafar; Ali Raza; Muhammad Madni; Asghar Nazir; Malaika Bibi; Abdullah K. Alanazi; A.N. Ahmed (Journal of Water Process Engineering, 2026)

Green-synthesized nanoparticles used to restore soil health and reprogram plant resilience - Babar Iqbal; Inamullah; Amir Abdullah Khan; Ali Raza Khan; Rasheed Akbar; Muhammad Sohail Memon; Guanlin Li; Daolin Du (Journal of Environmental Chemical Engineering, 2026)

Comparative insights into molecular characterization and resistance profiling of methicillin-resistant Staphylococcus aureus across dairy livestock in Pakistan - Muhammad Ijaz; Maria Batool; Muhammad Umar Javed; Hamza Rasheed; Arslan Ahmed; Ali Abdullah Jabir; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2026)

Integrating CMIP6 climate projections with community-based vulnerability assessment for climate resilience in Haripur, Pakistan - Syed Shujaat Ali; Sabahat Isha; Hamza Paracha; Abdullah Nadeem; Muhammad Atiq Ur Rehman Tariq (Theoretical and Applied Climatology, 2026)

Exploring the mechanisms of charged polysaccharides in regulating the microstructure, texture, and rheology of camellia oleosomes-based meat analogs - Shahzad Farooq; Abdullah; Muhammad Ijaz Ahmad; Usman Ali; Sumeng Wei; Jiawen Xue; Tin Nyawe Nyawe Hlaing; Quancai Sun; Ye Peng; Hui Zhang (Food Hydrocolloids, 2026)

Retraction Note: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2026)

Microfacies and diagenetic synthesis of the late early-middle eocene Kirthar Formation, Waziristan, Pakistan: implications for reservoir characterization - Fawad Ahmed; Abdullah Khan; Nowrad Ali; Muhammad Zafar; Ihtisham-ul-Haq; Mujahid Ahmed Khan (Carbonates and Evaporites, 2026)

Enhancing transgender mobility on public transport through equitable transport policies in a culturally conservative society - Nazam Ali; Muhammad Ashraf Javid; Ryan Cheuk Pong Wong; Muhammad Abdullah; Syed Sift-E-Hassan; Punyaanek Srisurin; Qudeer Hussain (Journal of Transport Geography, 2026)

Prevalence and mechanisms of antimicrobial resistance in respiratory bacterial pathogens of ruminants: a systematic review - Sophia Peter; Muhammad Zaki Zulkiffle; Bura Paul Thlama; Muhamad Hakim Mohd Ali Hanafiah; Faez Firdaus Jesse Abdullah; Juriah Kamaludeen; Suhaili Mustafa (Veterinary Research Communications, 2026)

Linalool exerts antiemetic effects via dopaminergic and serotonergic pathways: Evidence from chick model and molecular docking - Abdullah Al Fahmi; Khadija Akter; Imam Hossen Rakib; Sakib Hossain; Ali G. Alkhathami; Md. Sakib Al Hasan; Rakib Hossan; Iffat Ara; Md. Mizanur Rahaman; Muhammad Torequl Islam (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Linalool (LIN), a naturally occurring monoterpene alcohol found in aromatic plants, exhibits diverse pharmacological properties, yet its antiemetic potential remains underexplored. In this study, we investigated the antiemetic efficacy of LIN using both in vivo and in silico approaches. Emesis was induced in chicks via oral administration of copper sulfate pentahydrate (50 mg/kg), and LIN was tested at doses of 25, 50, and 100 mg/kg. Its effects were compared against the standard antiemetics domperidone (DOM, 7 mg/kg) and ondansetron (OND, 5 mg/kg). Results demonstrated that LIN at 100 mg/kg significantly prolonged the emetic latency and reduced the number of retches. Notably, co-administration of LIN (50 mg/kg) with DOM significantly ( p < 0.05) produced the most potent effect, yielding the highest latency and lowest number of retches, reflecting a synergistic interaction. Molecular docking studies revealed a strong binding affinity of LIN to the dopamine D2 receptor (− 6.4 kcal/mol) and moderate binding to the 5-HT3 receptor (− 5.3 kcal/mol), suggesting involvement of both dopaminergic and serotonergic mechanisms. These findings collectively indicate that LIN possesses significant antiemetic activity and may offer a plant-derived alternative for emesis control.

Anti-arthritic and anti-inflammatory effects of BMZD-2CPE in a CFA and carrageenan-induced animal model - Samiullah Wazir; Farah Abid; Aisha Mobashar; Arham Shabbir; Muhammad Awais; Humaira Nadeem; Hafiz Aamir Ali Kharl; Esmael M. Alyami; Amir Bouallegue; Norah Hamdi; Mohammed Bourhia; Abdullah R. Alanzi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Unveiling Hidden Threats: Molecular Detection and Genetic Diversity of Hepatozoon spp. and Toxoplasma Gondii in Wild Rodents of Saudi Arabia and Their Ectoparasites - Maryam Ijaz; Samia Q. Alghamdi; Abdullah D Alanazi; Mubashra Salim; Muhammad Naeem; Muhammad Ali; Shabana Mukhtiar; Kasim Sakran Abass; Hira Muqaddas; Adil Khan; Furhan Iqbal (Acta Parasitologica, 2026)

Rift Valley fever in Mauritania and Senegal: A One Health imperative - Muhammad Abdullah Ali; Zaryab Bacha; Fatima Sajjad (Infectious Diseases, 2026)

Short dry period improves postpartum energy balance and reproduction but reduces milk yield in dairy cows - Melad Ahmed; Amjad Riaz; Nasim Ahmad; Muhammad Naveed ul Haque; Hifz ul Rahman; Muhammad Yaseen; Talha Ashraf; Muhammad Abdullah; Ali Hassan; Ali Husnain (Theriogenology, 2026)

Exploring microbiological transformation of glutamate to γ-aminobutyric acid unleashed by a potential Lactobacillus spp. isolated from commercial cheese samples - Sikander Ali; Taha Shafi; Iram Liaqat; Muhammad Usman Ahmad; Ifrah Shabbir; Tariq Aziz; Maha Alharbi; Ashwag Shami; Fahad Al-Asmari; Ibrahim Faisal Halawani; Abdullah A. Alqasem; Reham M. Mashat; et al. (International Dairy Journal, 2026)

Extended reduced versus full-dose treatment with factor Xa inhibitors in patients with venous thromboembolism: a GRADE-assessed systematic review and meta-analysis of randomized controlled trials - Umama Alam; Muhammad Abdullah Ali; Muhammad Ansab; Shree Rath; Fazia Khattak; Zaryab Bacha; Hafiza Tooba Siddiqui; Fatima Sajjad; Abdullah Afridi; Zarar Ahmad Khan Afridi; Osama Ahmad; Abdul Moiz; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Bentonite clay in aflatoxin mitigation: advances, efficiency and perspectives - Syed Ali Raza Naqvi; Muhammad Kaleem Khan Khosa; Ameer Fawad Zahoor; Matloob Ahmad; Ariba Abdullah; Muhammad Ramzan Saeed Ashraf Janjua; Syed Ansar Abidi; Fatma Mohamed Ameen Khalil; Mohamed Fawzy Ramadan; João Miguel Rocha (Archives of Microbiology, 2026)

Optimizing tree crown density of finite coastal vegetation patches for enhanced tsunami mitigation - Fakhar Muhammad Abbas; Ali Abdullah Zaid Aldrees; Sohail Iqbal; Amina; Muhammad Atiq Ur Rehman Tariq; Naveed Anjum; Mujahid Iqbal; Usman Ghani; Ghufran Ahmed Pasha (Natural Hazards, 2025)

Improving Soil Fertility, Seed Yield, and Oil Quality of Sunflower Through Application of Processed Animal Manure Under Rainfed Conditions - Ghulam Abbas Shah; Mughees Mustafa; Zheli Ding; Zahid Mahmood; Faheem Khan; Shujaat Hussain Khan; Safdar Ali; Ghulam Mustafa Shah; Imran Mahmood; Muhammad Bilawal Junaid; Munirah Abdullah Al-Dosary; Muhammad Habib Ur Rehman; et al. (International Journal of Plant Production, 2025)

Sustainable cementless concrete reinforced with recycled steel fibers for spun-cast precast pipes: an innovative solution - Safeer Abbas; Moncef Nehdi; Ali Ahmed; Muhammad Abdullah Khan; Muhammad Mubashir Ajmal; Ammad Amir; Muhammad Zain Kashif; Qura tul Ain (Innovative Infrastructure Solutions, 2025)

Diversity of arthropods fauna in correlation to abiotic factors in wheat crop - Dilbar Hussain; Bushra Khalid; Muhammad Asrar; Usama Saleem; Wafa Abdullah Hamad Alkherb; Muhammad Saleem; Hina Anwar; Saddam Hussain; Muhammad Sohail Qadir; Mubshar Saleem; Khalid Ali Khan; Hamed A. Ghramh; et al. (International Journal of Tropical Insect Science, 2025)

Avian influenza outbreak in Cambodia: a public health concern - Muhammad Abdullah Ali; Alishba Hameed; Umama Alam; Zaryab Bacha; Ahmad Khan; Sangeen Khan (Infectious Diseases, 2025)

Comprehensive ampelographic and biochemical profiling of exotic grapevine (Vitis vinifera L.) cultivars grown under semi-arid conditions - Ubaid Abdul Khaliq; Irfan Ali; Abdel‑Halim Ghazy; Muhammad Tahir Akram; Mahmood-ul-Hassan; Haider Ali; Umer Habib; Tanveer Hussain; Kotb A. Attia; Sajid Fiaz; Abdullah A. Al-Doss; Muhammad Uzair; et al. (Genetic Resources and Crop Evolution, 2025)

Integrated PSInSAR and SBAS-InSAR analysis for landslide detection and monitoring - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; M. Abdullah-Al-Wadud; Aqil Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

The Role of Silver Nanoparticles and Bacillus subtilis in Modulating Morpho–Physio–Biochemical Responses in Wheat (Triticum aestivum L.) Under Arsenic Stress - Mohammad K. Okla; Sadia Javed; Muhammad Faran Tahir; Ibrahim A. Saleh; Muhammad Anas; Muhammad Hamzah Saleem; Temoor Ahmed; Abdulrahman Abdullah Alatar; Bandar M. AlMunqedhi; Shafaqat Ali (Journal of Soil Science and Plant Nutrition, 2025)
Soil contamination with toxic heavy metals [such as arsenic (As)] is becoming a serious global problem because of the rapid development of the social economy. Although plant growth-promoting rhizo-bacteria (PGPR) and nanoparticles (NPs) are the major protectants to alleviate metal toxicity, the study of these chemicals in combination to ameliorate the toxic effects of As is limited. Therefore, the present study was conducted to investigate the effects of different levels of Bacillus subtilis (5 and 10 mg L –1 ) and silver (Ag)–NPs (10 and 20 mg kg –1 ) on morpho-physiological and antioxidative defense attributes, which was spiked with different levels of As [0 mM (i.e., no As), 100, and 200 mg kg –1 ] in wheat ( Triticum aestivum L.) seedlings. Results from the present study showed that the increasing levels of As in the soil significantly ( P < 0.05) decreased plant growth and biomass, photosynthetic pigments, gas exchange attributes, sugars, and nutritional contents from the roots and shoots of the plants. In contrast, increasing levels of As in the soil significantly ( P < 0.05) increased oxidative stress indicators in term of malondialdehyde (MDA), hydrogen peroxide (H 2 O 2 ), and electrolyte leakage (EL), and also increased organic acid exudation patter in the roots of T. aestivum . The negative impact of As toxicity can overcome the application of B . subtilis and Ag − NPs, which ultimately increased plant growth and biomass by capturing the reactive oxygen species (ROS), and decreased oxidative stress in T. aestivum by decreasing the As contents in the roots and shoots of the plants. Research findings, therefore, suggest that the combined application of B . subtilis and Ag − NPs can ameliorate As toxicity in T. aestivum , resulting in improved plant growth and composition under metal stress, as depicted by balanced exudation of organic acids. Graphical Abstract

Investigating the development and success of Spodoptera Frugiperda (Lepidoptera: Noctuidae) on various wheat varieties: an age-stage specific life table analysis - Hamza Latif; Muhammad Arshad; Muhammad Irfan Ullah; Gulfam Yousaf; Nahdia Perveen; Wafa Abdullah Hamad Alkherb; Mohammed Ali Alshehri; Samy M. Sayed (International Journal of Tropical Insect Science, 2025)

Effect of Different Levels of Copper Oxide (CuO) Nanoparticles and Biochar on Soil’s Microbial Activities and Maize (Zea Mays L.) Growth - Muhammad Abdullah Aziz; Sana Zahra; Bilal Adil; Amir Naserin; Muhammad Asad Hameed; Ijaz Ali; Temoor Ahmed; Ajaz Ahmad (Journal of Soil Science and Plant Nutrition, 2025)

Exploring evolutionary perspectives and antibiogram analysis of biofilm-forming Staphylococcus aureus in goat mastitis - Muhammad Umar Javed; Muhammad Ijaz; Arslan Ahmed; Hamza Rasheed; Ali Abdullah Jabir; Maria Batool; Kehkshan Shahid; Ashraf Ali; Muhammad Talha (Veterinary Research Communications, 2025)

Formulation and Characterization of Isavuconazole-Loaded Chitosan/Sodium Alginate Nanoparticles for Dermal Delivery: in Vitro and in Vivo Evaluation for Enhanced Antifungal Therapy - Shahzad Khan; Asif Nawaz; Muhammad Khursheed Alam Shah; Muhammad Shahid Latif; Muhammad Haroon; Abdullah Khan; Tarek Mohamed Ali Elsayed (Journal of Pharmaceutical Innovation, 2025)

Cadmium Toxicity Affects Morpho-Physiological and Biochemical Attributes in Gladiolus grandiflorus L.: The Mitigating Roles of Exogenous Strigolactone (GR24) - Muhammad Ahsan; Muhammad Abdullah; Emanuele Radicetti; Mohamed Farouk Elsadek; Ali Bakhsh; Mateen Sajid; Mohammad Valipour; Aftab Jamal; Hera Gul; Syed Mohsin Abbas (Water, Air, & Soil Pollution, 2025)

Tailoring g-C3N4 properties through P and K co-doping: advancing photocatalytic CO2 reduction to CH4 - Ahmed Ismail; Muhammad Zahid; Bilal Ahmad; Salman Hayat; Sher Ali; Syed ul Hasnain Bakhtiar; Abdullah N. Alodhayb; Xiaoqiang Wu; Qaisar Alam; Sharafat Ali; Liang Qiao (Chemical Engineering Journal, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Bioactive Metabolites from Radioresistant Bacterium Kocuria sp. TMM 11 and Their Role in Prevention of Ultraviolet-Induced Photodamages - Tayyaba Alam; Salah Ud Din; Muhammad Abdullah; Mahwish Ali; Malik Badshah; Muhammad Farman; Samiullah Khan; Fariha Hasan; Aamer Ali Shah (Current Microbiology, 2025)

Evaluation of genotoxicity and physicochemical variations of Eichhornia crassipes (Mart.) Solms exposed to paper-mill-contaminated wastewater - Harma Shah; Muhammad U. F. Awan; Zahid Mehmood; Noor Sana; Wasim Abbas; Adeel Ahmad; Abdullah Qasim; Annum Gul; Ali Hasnain; Hsi-Hsien Yang (Environmental Monitoring and Assessment, 2025)

Improved damage assessment of bridges using advanced signal processing techniques of CEEMDAN-EWT and Kernal PCA - Hamza Ahsan Abdullah; Muhammad Usman Hanif; Muhammad Usman Hassan; Janita Mahnoor Shahid; Shaukat Ali Khan; Ather Ali (Engineering Structures, 2025)

Optimization and partial purification of tannase from Bacillus licheniformis AS1 under submerged fermentation and its application - Aqsa Shafique; Hafiz Abdullah Shakir; Muhammad Irfan; Shaukat Ali; Muhammad Khan; Chaman Ara; Noor Khan (Systems Microbiology and Biomanufacturing, 2025)

Biological Approaches to Sustainable Management of Fusarium Wilt in Cotton - Iqra Javed; Muhammad Arslan Khan; Hasan Riaz; Shafqat Saeed; Muhammad Sajid; Muhammad Bashair; Zulqarnain Abbas; Haider Ali; Munirah Abdullah Al-Dosary; Muhammad Bilawal Junaid (Journal of Crop Health, 2025)

Genome wide and evolutionary analysis of ALOG gene family and its role during seed development and nodulation in response to rhizobium in soybean - Muhammad Zulfiqar Ahmad; Bushra Ahmad; Jamal Abdul Nasir; Arshad Jamil; Saqib Ali; Asma Gul; Abdullah A. Alarfaj; Sulaiman Ali Alharbi (Genetic Resources and Crop Evolution, 2025)

Synthetic bacterial communities regulate polyamine metabolism and genes encoding antioxidant defense system to enhance arsenic tolerance of rice - Hamad Khan; Zeeshan Khan; Ishmal Eman; Ijaz Ahmad; Tariq Shah; Guoping Wang; Lu Feng; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Muhammad Javed Ansari (South African Journal of Botany, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

Visible light active CdS/CuO nanocomposites for photocatalytic degradation of ciprofloxacin, H2 production and antimicrobial activity - Naveed Akhtar; Chaejin Choi; Muhammad Ateeq; Perveen Fazil; Noor S. Shah; Javed Ali Khan; Abdullah G. Al-Sehemi; Amir Zada; Muhammad Ishaq Ali Shah; Rabia Ikram; Changseok Han (Chemical Engineering Journal, 2025)

Chemically Degraded Soil: Strategies for Mitigating its Toxicity and Enhancing Sustainable Crop Production - Mavadat Hussain Alvi; Habib Ali; Kamran Haider; Adeel Hussain Chughtai; Muhammad Abdullah; Seema Batool; Shahid Rasool; Rana Noman Anwar; Sadam Hussain (Journal of Soil Science and Plant Nutrition, 2025)

In-vitro and in-vivo assessments of greenly synthesized iron oxide nanoparticles from Cascabela thevetia plant extract for the treatment of ventricular septal defect - Amina Abid; Muhammad Naveed; Tariq Aziz; Muhammad Aqib Shabbir; Hira Mubeen; Ayaz Ali Khan; Abdullah F Alsmari (South African Journal of Botany, 2025)

Pathways and risk analysis of arsenic and heavy metal pollution in riverine water: Application of multivariate statistics and USEPA-recommended risk assessment models - Kifayatullah Khan; Muhammad Sajawal Khan; Muhammad Younas; Muhammad Yaseen; Abdullah G. Al-Sehemi; Yasar N. Kavil; Chao Su; Niaz Ali; Afsheen Maryam; Ruoyu Liang (Journal of Contaminant Hydrology, 2025)

Synthesis and doping of alkali metals on MOF-74 for CO2 and CH4 pure and binary mixtures adsorption - Sami Ullah; Mohamad Azmi Bustam; Muhammad Sagir; Muhammad Rafi Raza; Saleem Nawaz; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Ahmad Mukhtar; Chong Li Feng; Muhammad Ayoub (Gas Science and Engineering, 2025)

Systematic implication of trichome morphology in alpine flora from Hindukush Mountain range - Muhammad Abdullah; Zahid Ullah; Syed Muhammad Iqbal Shah; Mushtaq Ahmad; Amjad Khan; Hussain Shah; Ateef Ullah; Shabir Ahmad; Mohammed Fahad Albeshr; Okezie Emmanuel; Hameed Ullah; Rahman Ali Khan (Genetic Resources and Crop Evolution, 2025)

A novel (−)-(2S)-7,4′-dihydroxyflavanone compound for treating age-related diabetes mellitus through immunoinformatics-guided activation of CISD3 - Abdur-Rehman Munir; Saad Ilyas Baig; Muhammad Asif Razzaq; Fatima Rauf; Yasir Ali; Syed Muhammad Abdullah Azam (Biogerontology, 2025)

Exploring the synergistic effect of NaOH/NaClO absorbent in a novel wet FGD scrubber to control SOx/NOx emissions - Muhammad Rizwan; Muhammad Faryad Ali; Muhammad Asif Nawaz; Mu He; Yueqin Song; Peng Jiang; Saif Ullah; Malik M. Abdullah Hassan; Xiaolong Zhou (Environmental Monitoring and Assessment, 2025)

Innovative transformation of palm oil biomass waste into sustainable biofuel: Technological breakthroughs and future prospects - Tonni Agustiono Kurniawan; Mehwish Ali; Ayesha Mohyuddin; Ahtisham Haider; Mohd Hafiz Dzarfan Othman; Abdelkader Anouzla; Hui Hwang Goh; Dongdong Zhang; Wei Dai; Faissal Aziz; Muhammad Imran Khan; Imran Ali; et al. (Process Safety and Environmental Protection, 2025)

A critical review of NO2 and AOD in major Asian cities: challenges, mitigation approaches and way forwards - Most Mastura Munia Farjana Jion; Abu Reza Md Towfiqul Islam; Mahir Shahrier; Md Yousuf Mia; Jannatun Nahar Jannat; Md Arfan Ali; Md Abdullah Al Masud; Md Firoz Khan; Muhammad Bilal; Abubakr M. Idris; Guilherme Malafaia (Air Quality, Atmosphere & Health, 2025)

Pharmacotherapeutic potential of bilobetin to combat chromium induced hepatotoxicity via regulating TLR-4, Nrf-2/Keap-1, JAK1/STAT3 and NF-κB pathway: A pharmacokinetic and molecular dynamic approach - Mahmoud El Safadi; Muhammad Faisal Hayat; Ali Akbar; Abdullah Nisar; Fuad M. Alzahrani; Khalid J. Alzahrani (Journal of Trace Elements in Medicine and Biology, 2024)

Fabrication and characterization of bioactive curdlan and sodium alginate films for enhancing the shelf life of Volvariella volvacea - Asif Ali Khan; Feng-Jie Cui; Muhammad Wajid Ullah; Abdul Qayum; Ibrahim Khalifa; Syed Asim Shah Bacha; Zheng-Zi Ying; Ismail Khan; Umar Zeb; Abdullah A. Alarfaj; Mohammad Javed Ansari; Yan Yang; et al. (Food Bioscience, 2024)

Advancements in sustainable production of biofuel by microalgae: Recent insights and future directions - Muhammad Abdullah; Zain Ali; Muhammad Talha Yasin; Kinza Amanat; Fatima Sarwar; Jallat Khan; Khurshid Ahmad (Environmental Research, 2024)

Zebrafish as an innovative model for exploring cardiovascular disease induction mechanisms and novel therapeutic interventions: a molecular insight - Shaukat Ali; Maryam Zulfiqar; Muhammad Summer; Mahnoor Arshad; Shehzeen Noor; Laiba Nazakat; Abdullah Javed (Molecular Biology Reports, 2024)

Removal of chlorpyrifos from aqueous medium using Ca-CuO@clay nanoflakes coated with deep eutectic solvent - Abdullah Zia; Umer Younas; Zahid Ali; Rabia Nazir; Faisal Ali; Aemin Irfan; Muhammad Pervaiz (Environmental Monitoring and Assessment, 2024)

Remote Sensing Assessment of Water Resources, Vegetation, and Land Surface Temperature in Eastern Saudi Arabia: Identification, Variability, and Trends - Mazen E. Assiri; Md Arfan Ali; Muhammad Haroon Siddiqui; Albandari AlZahrani; Lama Alamri; Abdullah Masoud Alqahtani; Ayman S. Ghulam (Remote Sensing Applications: Society and Environment, 2024)

Synergistic biochar and Serratia marcescens tackle toxic metal contamination: A multifaceted machine learning approach - Hamid Rehman; Aqib Hassan Ali Khan; Tayyab Ashfaq Butt; Muhammad Toqeer; Muhammad Bilal; Mahtab Ahmad; Ahmed Abdullah Alawi Al-Naghi; Enamur Rahim Latifee; Omar Ali Saad Algassem; Mazhar Iqbal (Journal of Environmental Management, 2024)

Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Zeshan Ali Sandhu; Umme Farwa; Muhammad Danish; Muhammad Asam Raza; Aqib Talib; Hifza Amjad; Rukhmah Riaz; Abdullah G. Al-Sehemi (Journal of Cleaner Production, 2024)

Analyzing Agricultural Land Use with Cellular Automata-MARCOV and Forecasting Future Marine Water Quality Index: A Case Study in East Coast Peninsular Malaysia - Mohd Saiful Samsudin; Azman Azid; Muhammad Amar Zaudi; Mohd Ridhwan Adam; Muhamad Shirwan Abdullah Sani; Shazlyn Millenana Saharuddin; Aminu Ibrahim; Mohd Fahmi Mohd Nasir; Mou Leong Tan; Nurul Izzati Mohd Ali (Water, Air, & Soil Pollution, 2024)

InGaN/GaN multi-quantum well nanowires: Enhanced trace-level NO2 detection for environmental and breath analysis - Arunkumar Shanmugasundaram; Muhammad Ali Johar; Changung Paeng; Yun-Jin Jeong; Ameer Abdullah; Jongsung Park; Sang-Wan Ryu; Changyong Yim; Dong-Weon Lee (Chemical Engineering Journal, 2024)

Response of cotton mealybug, Phenacoccus Solenopsis Tinsley (Sternorrhyncha: Pseudococcidae) to predators, neem oil, and synthetic insecticide under semi-field and field conditions - Muhammad Mamoon-ur-Rashid; Khalid Abdullah; Habib Ali; Muhammad Tariq; Adnan Noor Shah; Shahbaz Ali (International Journal of Tropical Insect Science, 2024)

Potential application of Ginkgo biloba extract as a green corrosion inhibitor for carbon steel reinforcement in chloride-polluted simulated concrete pore solution - Ambrish Singh; K.R. Ansari; Siham K. AbdelRahim; Ismat H. Ali; Brahim EL Ibrahimi; Abdullah K. Alanazi; Muhammad Younas; Yuanhua Lin (Process Safety and Environmental Protection, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

Evaluation of drought hazards and coping strategies adopted by pastoral communities in the Cholistan Rangeland of Pakistan - Muhammad Farooq Azhar; Muhammad Junaid Faiz; Ehsan Ali; Abida Aziz; Muhammad Akbar; Ghulam Raza; Muhammad Abdullah; Muhammad Muzammil Habib; Muhammad Farooq Akram (Environmental Development, 2024)

Insights into the involvement of male Hyalomma anatolicum ticks in transmitting Anaplasma marginale, lumpy skin disease virus and Theileria annulata - Sikandar Ali; Abdullah Saghir Ahmad; Kamran Ashraf; Jawaria Ali Khan; Muhammad Imran Rashid (Tropical Animal Health and Production, 2024)

Silver oxide doped iron oxide/alginate nanocomposite coated cotton cloth for selective catalytic reduction of potassium ferricyanide - Esraa M. Bakhsh; Kalsoom Akhtar; Sher Bahadar Khan; Abdullah M. Asiri; Tahseen Kamal; Muhammad Bilal; Shahid Ali Khan (Chemosphere, 2024)

Exploring Bacillus mycoides PM35 efficacy in enhancing rice (Oryza sativa L.) response to different types of microplastics through gene regulation and cellular fractionation - Dalal Nasser Binjawhar; Rana M. Alshegaihi; Aishah Alatawi; Muneefah Abdullah Alenezi; Abida Parveen; Muhammad Adnan; Baber Ali; Khalid Ali Khan; Shah Fahad; Eman Fayad (Environmental Science and Pollution Research, 2024)

Organic waste-to-bioplastics: Conversion with eco-friendly technologies and approaches for sustainable environment - Zain Ali; Muhammad Abdullah; Muhammad Talha Yasin; Kinza Amanat; Khurshid Ahmad; Ishfaq Ahmed; Muther Mansoor Qaisrani; Jallat Khan (Environmental Research, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Effects of agro based organic amendments on growth and cadmium uptake in wheat and rice crops irrigated with raw city effluents: Three years field study - Hiba Shaghaleh; Muhammad Azhar; Muhammad Zia-ur-Rehman; Yousef Alhaj Hamoud; Ammar Ali Adam Hamad; Muhammad Usman; Muhammad Rizwan; Jean Wan Hong Yong; Hesham F. Alharby; Abdullah G. Al-Ghamdi; Basmah M. Alharbi (Environmental Pollution, 2024)

Molecular prevalence of vector borne bacterial pathogens in the blood samples of wild rodent species trapped from Saudi Arabia - Abdul Ghafar; Samia Q. Alghamdi; Abdullah D. Alanazi; Syed Muhammad Zukhruf Qousain; Maryam Ijaz; Muhammad Naeem; Muhammad Ali; Hira Muqaddas; Adil Khan; Furhan Iqbal (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Tracking the Feeding Mechanism of Sap-Sucking Insect-Pests Through Electropenetrography (EPG) - Usama Bin Tayyab; Muhammad Jalal Arif; Muhammad Dildar Gogi; Shamim Akhtar; Muhammad Jawad Abdullah; Faisal Ali (Journal of Insect Behavior, 2024)

An Aedes–Anopheles Vaccine Candidate Supplemented with BCG Epitopes Against the Aedes and Anopheles Genera to Overcome Hypersensitivity to Mosquito Bites - Muhammad Naveed; Urooj Ali; Tariq Aziz; Rida Naveed; Sarmad Mahmood; Muhammad Mustajab Khan; Metab Alharbi; Thamer H. Albekairi; Abdullah F. Alasmari (Acta Parasitologica, 2024)

Preharvest melatonin application mitigates arsenic-induced oxidative stress and improves vase life of tuberose (Polianthes tuberosa L.) cut flowers - Faisal Zulfiqar; Anam Moosa; Hayssam M. Ali; Antonio Ferrante; Muhammad Mudassir Nazir; Abdullah Makhzoum; Tarek M.A. Soliman (South African Journal of Botany, 2023)

Assessing coastal bathymetry and climate change impacts on coastal ecosystems using Landsat 8 and Sentinel-2 satellite imagery - Kasypi Mokhtar; Lai Fatt Chuah; Mohd Azhafiz Abdullah; Olakunle Oloruntobi; Siti Marsila Mhd Ruslan; Gadah Albasher; Atif Ali; Muhammad Saeed Akhtar (Environmental Research, 2023)

Sequence variants in different genes underlying Bardet-Biedl syndrome in four consanguineous families - Amjad Ali; Abdullah; Muhammad Bilal; Emily Kathryn Mis; Saquib Ali Lakhani; Wasim Ahmad; Imran Ullah (Molecular Biology Reports, 2023)

Seaweed Application Enhanced the Growth and Yield of Pea (Pisum sativum L.) by Altering Physiological Indices - Safina Naz; Hafiza Muniba Din Muhammad; Muhammad Ramzan; Bushra Sadiq; Riaz Ahmad; Saqib Ali; Abdulaziz Abdullah Alsahli; Muhammad Ahsan Altaf (Journal of Soil Science and Plant Nutrition, 2023)

Correction to: Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman Khokhar; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Correction to: Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

Comparison of As removal efficiency and health risks from aqueous solution using as-synthesized Fe0 and Cu0: modelling, kinetics and reusability - Behzad Murtaza; Asad Ali; Muhammad Imran; Abdullah A. Al-Kahtani; Zeid A. ALOthman; Natasha Natasha; Muhammad Shahid; Noor S. Shah; Muhammad Asif Naeem; Sajjad Ahmad; Ghulam Murtaza (Environmental Geochemistry and Health, 2023)

Combination of advanced coagulation Fe(VI) and UF membrane to effectively remove organic compounds and mitigate biofouling during harmful algal blooms - Abdullah H. Alshahri; M. Obaid; Abdullah H.A. Dehwah; Thomas M. Missimer; Muhammad Ali; Noreddine Ghaffour (Desalination, 2023)

Transcriptomic analysis of Ralstonia solanacearum in response to antibacterial volatiles of Bacillus velezensis FZB42 - Hafiz Abdul Samad Tahir; Qurban Ali; Faheem Uddin Rajer; Qaisar Shakeel; Waqqas Gillani; Rana Binyamin; Hafiz Muhammad Abdullah Tayyab; Abdur Rashid Khan; Qin Gu; Xuewen Gao; Huijun Wu (Archives of Microbiology, 2023)

LS8pyCalc: semi-automated Python calculator to retrieve land surface temperature, cross verified through in situ and MODIS datasets - Mamoon Ur Rasheed; Syed Amer Mahmood; Rao Mansor Ali Khan; Muhammad Abdullah Sohl (Arabian Journal of Geosciences, 2023)

Assessment of the phycosphere microbial dynamics of microbial community associated with red algae culture under different cultural conditions - Asadullah Gujar; Muhammmad Ahsan Asghar; Muneefah Abdullah Alenezi; Muhammad Saleem Kubar; Kashif Ali Kubar; Ali Raza; Khansa Saleem; Hafiz Hassan Javed; Abu Zar Ghafoor; Muhammad Iftikhar Hussain; Abd Ullah; Hongli Cui; et al. (Environment, Development and Sustainability, 2023)

Aspartame, a Synthetic Dipeptide Mediated Biochemical and Histopathological Alterations in Hepato-nephric Tissues of Mice and Pharmaceutical Intervention by Sesame Oil - Chaman Ara; Memoona Arshad; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Summer; Muhammad Khan; Iram Liaqat; Madeeha Arshad (International Journal of Peptide Research and Therapeutics, 2023)

Diversity of arthropods in citrus orchards of Sargodha, Pakistan: Use of different trapping techniques - Muhammad Irfan Ullah; Muhammad Arshad; Asad Abdullah; Nimra Altaf; Syed Muhammad Ali Zahid; Muhammad Afzal (International Journal of Tropical Insect Science, 2023)

Microplastics in soil differentially interfere with nutritional aspects of chilli peppers - Khadiga Alharbi; Muhammad Aqeel; Noreen Khalid; Atia Nazir; Muhammad Kashif Irshad; Fahad Mohammed Alzuaibr; Haifa AbdulAziz Sakit AlHaithloul; Noreen Akhter; Omar Mahmoud Al-Zoubi; Muhammad Qasim; Khalid M.Al Syaad; Manal Abdullah AlShaqhaa; et al. (South African Journal of Botany, 2023)

Optimization of viscosity of titania nanotubes ethylene glycol/water-based nanofluids using response surface methodology - Abdullah Bin Mahfouz; Abulhassan Ali; Muhammad Mubashir; Abdulkader S. Hanbazazah; Mustafa Alsaady; Pau Loke Show (Fuel, 2023)

Genetic modification strategies for enhancing plant resilience to abiotic stresses in the context of climate change - Amman KhokharVoytas; Muhammad Shahbaz; Muhammad Faisal Maqsood; Usman Zulfiqar; Nargis Naz; Usama Zafar Iqbal; Maheen Sara; Muhammad Aqeel; Noreen Khalid; Ali Noman; Faisal Zulfiqar; Khalid M. Al Syaad; et al. (Functional & Integrative Genomics, 2023)

Flavonoids: a review on biosynthesis and transportation mechanism in plants - Muhammad Aamir Manzoor; Irfan Ali Sabir; Iftikhar Hussain Shah; Muhammad Waheed Riaz; Shamsur Rehman; Cheng Song; Gouhui Li; M. Sanaullah Malik; Ghulam Abbas Ashraf; Muhammad Sajjad Haider; Yunpeng Cao; Muhammad Abdullah (Functional & Integrative Genomics, 2023)

A framework to identify and prioritise the key sustainability indicators: Assessment of heating systems in the built environment - Mohammad Hosein Abbasi; Badr Abdullah; Raúl Castaño-Rosa; Muhammad Waseem Ahmad; Ali Rostami (Sustainable Cities and Society, 2023)

An approach to assess offshore wind power potential using bathymetry and near-hub-height reanalysis data - Zia ul Rehman Tahir; Muhammad Abdullah; Sajeer Ahmad; Ammara Kanwal; Muhammad Farhan; Usama Bin Saeed; Tariq Ali; Imran Amin (Ocean Engineering, 2023)

Retraction notice to “Melatonin rescues the mice brain against cisplatin-induced neurodegeneration, an insight into antioxidant and anti-inflammatory effects” [Neurotoxicology 87 (2021) 1–10] - Muhammad Zakria; Nasir Ahmad; Lina Tariq Al Kury; Abdullah Alattar; Zia Uddin; Sami Siraj; Shakir Ullah; Reem Alshaman; Muhammad Imran Khan; Fawad Ali Shah (NeuroToxicology, 2023)

“Retraction notice to Carveol ameliorates mercury-induced oxidative stress, neuroinflammation, and neurodegeneration in a mouse brain” NeuroToxicology 92 (2022) 212–226 - Abdullah Alattar; Arooj Mohsin Alvi; Sajid Rashid; Nadia Hussain; Mehreen Gul; Muhammad Ikram; Atif Ali Khan Khalil; Reem Alshaman; Fawad Ali Shah; Shupeng Li; Jingbo Li (NeuroToxicology, 2023)

Transcriptomic and proteomic profiling reveals toxicity and molecular action mechanisms of bioengineered chitosan‑iron nanocomposites against Xanthomonas oryzae pv. oryzae - Temoor Ahmed; Luqiong Lv; Muhammad Noman; Hafiza Ayesha Masood; Muhammad Rizwan; Munazza Ijaz; Ashraf Atef Hatamleh; Munirah Abdullah Al-Dosary; Hayssam M. Ali; Jianping Chen; Bin Li (Pesticide Biochemistry and Physiology, 2023)

Correction to: Development and evaluation of sunscreen cream containing solid lipid nanoparticles of Spinacia oleraceae - Vijisha Taniyadukkam; Jobin Jose; Naseer Maliyakkal; Asmy Appadath Beeran; Muhammad Ali Abdullah Almoyad; Lotfi Aleya; Akshay Bandiwadekar (Environmental Science and Pollution Research, 2023)

Corrosion and bacterial growth mitigation in the desalination plant by imidazolium based ionic liquid: Experimental, surface and molecular docking analysis - Ambrish Singh; K.R. Ansari; Neeta Raj Sharma; Shivani Singh; Rahul Singh; Anu Bansal; Ismat H. Ali; Muhammad Younas; Abdullah K. Alanazi; Yuanhua Lin (Journal of Environmental Chemical Engineering, 2023)

Investigation of PT 58 and PEG-6000-based finned heat sinks for thermal management of electronics - Radhi Abdullah Lawag; Hafiz Muhammad Ali; Md Hasan Zahir; Bilal A. Qureshi (Journal of Cleaner Production, 2023)

Phenotypic and Genotypic Analysis of the Population of Phytophthora infestans in Bangladesh Between 2014 and 2019 - Md. Huzzatul Islam; Sangee Sarkar Shanta; Muhammad Iqbal Hossain; Muhammed Ali Hossain; Md. Monower Hossain; Ebna Habib Md. Shofiur Rahaman; Abdullah Al Mahmud; Md. Abdullah Yousuf Akhond; Louise Sullivan; David E. L. Cooke; Geert J. T. Kessel; Louise R. Cooke; et al. (Potato Research, 2023)
In Bangladesh, the third largest producer of potatoes in Asia, late blight, caused by Phytophthora infestans , is the major constraint to production. Nevertheless, there is a lack of published information on the pathogen population. A collection of 69 isolates obtained from samples of infected potato foliage collected in 2018–2019 varied significantly in their aggressiveness to detached potato leaflets and tuber slices of cv. Diamant. On leaflets, most isolates were highly aggressive, colonizing more than half the surface in 7 days. On tuber slices, while some isolates were highly aggressive, those collected in 2019 were less so. There was a significant effect of the locations from which the isolates were obtained on aggressiveness to both leaflets and tuber slices, but aggressiveness to leaflets and to tuber slices was not significantly correlated. All isolates were A2 mating type and either intermediate (38%) or resistant (62%) in sensitivity to the fungicide metalaxyl . A subset of 24 isolates all had mitochondrial DNA haplotype Ia. Samples of P. infestans DNA (124) from infected potato foliage obtained from Bangladesh (2014–2019) were genotyped by 12-plex SSR. The vast majority (95%) were assigned to EU_13_A2, which was present in every year in which samples were collected. Numerous EU_13_A2 variants were identified, many specific to Bangladesh. Six samples (from 2017 to 2019) had genotypes distinct from EU_13_A2 and with no close match to known European lineages. It is concluded that the current P. infestans population of Bangladesh is dominated by the aggressive lineage EU_13_A2, also dominant in India and Pakistan. The implications of this for control of late blight are discussed.

Development and evaluation of sunscreen cream containing solid lipid nanoparticles of Spinacia oleraceae - Vijisha Taniyadukkam; Jobin Jose; Naseer Maliyakkal; Asmy Appadath Beeran; Muhammad Ali Abdullah Almoyad; Lotfi Aleya; Akshay Bandiwadekar (Environmental Science and Pollution Research, 2023)

High pressure CO2 adsorption onto Malaysian Mukah-Balingian coals: Adsorption isotherms, thermodynamic and kinetic investigations - Mustafa Abunowara; Mohamad Azmi Bustam; Suriati Sufian; Muhammad Babar; Usama Eldemerdash; Ahmad Mukhtar; Sami Ullah; Mohammed Ali Assiri; Abdullah G. Al-Sehemi; Su Shiung Lam (Environmental Research, 2023)

Influence of stress relief due to deep excavation on a brick masonry wall: 3D numerical predictions - Mukhtiar Ali Soomro; Dildar Ali Mangnejo; Abdullah Saand; Naeem Mangi; Muhammad Auchar Zardari (European Journal of Environmental and Civil Engineering, 2022)

Adenosine A2A receptor as a potential target for improving cancer immunotherapy - Muhammad Atif; Abdullah Alsrhani; Farrah Naz; Muhammad Ikram Ullah; Ayman Ali Mohammed Alameen; Muhammad Imran; Hasan Ejaz (Molecular Biology Reports, 2022)

Characterization of Corn Oil Using Fluorescence Spectroscopy - Saud Abdullah; Muhammad Asif; Hina Ali; Raheel Ali; Muhammad Saleem (Journal of Fluorescence, 2022)

Side-Scan Sonar Coupled with Scuba Diving Observation for Enhanced Monitoring of Benthic Artificial Reefs along the Coast of Terengganu, Peninsular Malaysia - Azizi Ali; Muhammad Ruzi Abdullah; Che Din Mohd Safuan; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok; Mohd Fadzil Mohd Akhir; Roslan Latif; Azri Muhamad; Tan Hock Seng; Adina Roslee; Khaira Ismail (Journal of Marine Science and Engineering, 2022)
Since the 1970s, artificial reef (AR) deployment has been one of the common approaches to augment the local production of coastal fish in Malaysia. However, there is a lack of strategy to assess and evaluate the success of pre-deployed AR. Realizing the need for an effective qualitative and quantitative monitoring and evaluation of AR, this study proposes side-scan sonar coupled with scuba diving observation for the enhanced monitoring of pre-deployed Bioceramic Korean (BK) AR along the coast of Terengganu, Peninsular Malaysia. This method employs an integrated side-scan sonar with a data acquisition system for the detection of the precise location of the BK AR which were deployed at Tukun Telaga Batin off the Terengganu coastline in 2003 by the Fisheries Development Authority of Malaysia (FDAM). Following the determination of the exact location of three BK AR areas, a scuba diving team was sent to survey the physical conditions of the AR and assess the feasibility of the AR as an artificial habitat for marine life. The scan sonar images were compared with the captured photographs and videos acquired during the scuba diving session for a comprehensive value-added assessment. The collected data from the scuba diving session were also processed to measure the fish diversity, the fish biomass, and identify the fish community surrounding the AR. Based on the results, the BK AR remained in extremely good condition, physically intact, without significant breakage or damage, and with no major subsidence into the sediment after 19 years of deployment. A total of 108 BK AR modules were detected in three large groups using the mosaicked sonar images. Following cross-examination to validate the AR measurements using the AR’s shadows on the seafloor, the height of the BK AR consistently ranged from 1.7 m to 1.8 m. In addition, 34 species of fish from 14 families and 26 genera were identified, with most species classified as reef-associated (RA) fish with a biomass value of 1173.31 ± 1136.69 kg m−3, indicating the successfulness of the BK AR as fish-aggregating devices (FADs). The growth of hard corals on top of the bioceramic plate of the AR module further supported the diversified community of marine life surrounding the BK AR. In conclusion, the side-scan sonar coupled with scuba diving observation demonstrates an effective qualitative and quantitative technique for the monitoring and evaluation of pre-deployed AR. This strategy is recommended to be utilized to determine the success of pre-deployment AR.

Fabrication of Fe/Bi bimetallic magnetic nano-oxides (IBBMNOs) as efficient remediator for hexavalent chromium from aqueous environment - Ali Muhammad Mahar; Esra Alveroglu; Aamna Balouch; Farah Naz Talpur; Abdullah.; Muhammad Saqaf Jagirani (Environmental Science and Pollution Research, 2022)

Wildlife trade and the establishment of invasive alien species in Indonesia: management, policy, and regulation of the commercial sale of songbirds - Vincent Nijman; Ahmad Ardiansyah; Penthai Siriwat; Hélène Birot; Swiss Winnasis; Evros Damianou; Muhammad Ali Imron; Abdullah Langgeng; Beth Lewis; K. Anne-Isola Nekaris (Biological Invasions, 2022)
In Southeast Asia, mynas (genus Acridotheres ) are amongst the most invasive bird species. Information is largely lacking as to where they have established themselves. The spread of invasive, non-native mynas is partially or largely driven by the massive trade in these species as songbirds. While preventing unintentional introductions early is the most effective management option, these species continue to be traded in bird markets throughout the region. We focus on the trade of native and non-native species of mynas, and the establishment of non-native mynas on the Indonesian islands of Java, Bali, and Lombok. Between 2016 and 2019, through field surveys and use of citizen science data (e.g., Burungnesia, iNaturalist, birding reports), we assessed where non-native mynas have been recorded in the wild on these three islands; through bird market surveys we established in which cities these birds are traded. We recorded common myna in Yogyakarta, one of our three survey areas. Combining all records, the areas where alien invasive mynas are established are Greater Jakarta (common and jungle myna), Yogyakarta (common myna), Bali (common and bank myna) and Lombok (common and Javan myna). Two-thirds of the records come from farmlands, home gardens and urbanised areas. In the bird markets, we recorded ~ 23,000 mynas of five species for sale, with Greater Jakarta, Bali and Lombok standing out as areas with high numbers of potentially invasive alien species offered for sale. Restrictions on the sale of wild-caught birds are not adhered to. Well-intended policies concerning the breeding and sale of legally protected species, whereby 10% of the stock is bred to be released in the wild, exacerbate the risk of the establishment of non-native species. We surmise that one of the most effective ways to reduce the risk of the accidental or deliberate release of potentially invasive alien mynas (and indeed other birds) into the wild is for governments and conservationists to work more closely with the retailers who hold the key to informing and educating consumers.

Biochar in Combination with Nitrogen Fertilizer is a Technique: To Enhance Physiological and Morphological Traits of Rice (Oryza sativa L.) by Improving Soil Physio-biochemical Properties - Izhar Ali; Quan Zhao; Ke Wu; Saif Ullah; Anas Iqbal; He Liang; Jing Zhang; Ihsan Muhammad; Amanullah; Abdullah Khan; Asad Ali Khan; Ligeng Jiang (Journal of Plant Growth Regulation, 2022)

Genome-wide identification and comparative analysis of MATE gene family in Cucurbitaceae species and their regulatory role in melon (Cucumis melo) under salt stress - Iftikhar Hussain Shah; Muhammad Aamir Manzoor; Irfan Ali Sabir; Muhammad Ashraf; Fazal Haq; Samiah Arif; Muhammad Abdullah; Qingliang Niu; Yidong Zhang (Horticulture, Environment, and Biotechnology, 2022)

Water-saturated zone recognition using integrated 2D electrical resistivity tomography, borehole, and aerial photogrammetry in granite deposit, Malaysia - Muhammad Junaid; Rini Asnida Abdullah; Radzuan Sa’ari; Wahid Ali; Hafeezur Rehman; kausar Sultan Shah; Mahmut Sari (Arabian Journal of Geosciences, 2022)

Mass Transfer Kinetics and Mechanisms of Phosphate Adsorbed on Waste Mussel Shell - Nur Atikah Abdul Salim; Mohamad Ali Fulazzaky; Mohd Hafiz Puteh; Mohd Hairul Khamidun; Abdull Rahim Mohd Yusoff; Noorul Hudai Abdullah; Mohammad Fulazzaky; Muhammad Abbas Ahmad Zaini (Water, Air, & Soil Pollution, 2022)

Reliability of the Mass Transfer Factor Models to Describe the Adsorption of NH4+ by Granular Activated Carbon - Mohamad Ali Fulazzaky; Nur Atikah Abdul Salim; Mohd Hafiz Puteh; Mohd Hairul Khamidun; Abdull Rahim Mohd Yusoff; Mohammad Fulazzaky; Noorul Hudai Abdullah; Muhammad Abbas Ahmad Zaini (International Journal of Environmental Research, 2022)

RETRACTED ARTICLE: Novel acetamide derivatives of 2-aminobenzimidazole prevent inflammatory arthritis in rats via suppression of pro-inflammatory mediators - Aymun Madni Zubair; Muhammad Nasir Hayat Malik; Waqas Younis; Muhammad Atif Hayat Malik; Shah Jahan; Ishtiaq Ahmed; Alamgeer Yuchi; Muhammad Naveed Mushtaq; Romeeza Tahir; Muhammad Bilal Sarwar; Muhammad Roman; Ayaz Ali Khan; et al. (Inflammopharmacology, 2022)

Comprehensive review on naringenin and naringin polyphenols as a potent anticancer agent - Abdur Rauf; Mohammad Ali Shariati; Muhammad Imran; Kashif Bashir; Shahid Ali Khan; Saikat Mitra; Talha Bin Emran; Kamala Badalova; Md. Sahab Uddin; Mohammad S. Mubarak; Abdullah S. M. Aljohani; Fahad A. Alhumaydhi; et al. (Environmental Science and Pollution Research, 2022)

An alternative approach to estimate river cross-sections using LIDAR-based digital elevation model - Mohd Talha Anees; Ahmad Farid Bin Abu Bakar; Mohammad Muqtada Ali Khan; Muhammad I. Syakir; K. Abdullah; Mohd Nawawi Mohd Nordin; Kamal Abdelrahman; Ahmed M. Eldosouky; Peter Andráš; Nasehir Khan Bin E.M. Yahaya; Zubaidi Johar; Fatehah Mohd Omar; et al. (Hydrological Sciences Journal, 2022)

Functionalized multi-walled carbon nanotubes for oil spill cleanup from water - Thamer Adnan Abdullah; Tatjana Juzsakova; Sanaa A. Hafad; Rashed Taleb Rasheed; Noor Al-Jammal; Muhammad Ali Mallah; Ali Dawood Salman; P. C. Le; Endre Domokos; Mustafa Aldulaimi (Clean Technologies and Environmental Policy, 2022)
The growing global economy resulted in an incessant increase in transportation and exploitation of oil. Hence, the oil spillage has been considered a serious threat to aquatic and terrestrial ecosystems. Therefore, water purification has been considered a major challenge around the world. There are numerous classical methods available for oil removal from water, but owing to multiple defects and disadvantages, research efforts have focused to find such adsorbents which can improve oil adsorption capability. Traditional adsorbent material typically applied in oil removal includes activated carbon, organoclays, wool, zeolites, etc. These materials suffer from several drawbacks such as low absorption capacity, non-selective absorption, and complicated reusability, whereas nano-adsorbents offer multiple advantages such as having multiple sorption sites, large surface area, short intra-particle diffusion distance, tuneable pore size, and ease of low-temperature modification. Multi-walled carbon nanotubes (MWCNTs) are extensively used adsorbent materials with a strong affinity for the removal of organic pollutants. The functionalization MWCNTs further increase the sorption capacity of adsorbents manifolds to remove organic materials. These nanocomposites are also compatible with green materials and considered environmentally friendly adsorbents. This review paper aims at providing an insight to understand the properties of the MWCNTs and their potential use to adsorb hydrocarbons from water. Moreover, the synthesis methods of those materials, their modification procedures including the functionalization with metal oxide nanoparticles, and applications are also discussed in detail. Graphic abstract

Ameliorative effect of ethoxylated chalcone-based MAO-B inhibitor on behavioural predictors of haloperidol-induced Parkinsonism in mice: evidence of its antioxidative role against Parkinson’s diseases - Naseer Maliyakkal; Uzma Saleem; Fareeha Anwar; Muhammad Ajmal Shah; Bashir Ahmad; Filzah Umer; Mohammad Ali Abdullah Almoyad; Della Grace Thomas Parambi; Asmy Appadath Beeran; Lekshmi R Nath; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

In vitro α-glycosidase and urease enzyme inhibition profile of some selected medicinal plants of Pakistan - Abdur Rauf; Saud Bawazeer; Muhammad Naseer; Fahad A. Alhumaydhi; Abdullah S. M. Aljohani; Aamir Habib; Raheem Khan; Urooj Jehan; Muhammad Nasimullah Qureshi; Majid Khan; Umar Farooq; Amirzhan Kassenov; et al. (Natural Product Research, 2021)

Aging and its treatment with vitamin C: a comprehensive mechanistic review - Shumaila Mumtaz; Shaukat Ali; Hafiz Muhammad Tahir; Syed Akif Raza Kazmi; Hafiz Abdullah Shakir; Tafail Akbar Mughal; Samaira Mumtaz; Muhammad Summer; Muhammad Adeel Farooq (Molecular Biology Reports, 2021)

Seed Priming with Sodium Nitroprusside and H2O2 Confers Better Yield in Wheat Under Salinity: Water Relations, Antioxidative Defense Mechanism and Ion Homeostasis - Noman Habib; Qasim Ali; Shafaqat Ali; Muhammad Zulqarnain Haider; Muhammad Tariq Javed; Mubashra Khalid; Rashida Perveen; Abdulaziz Abdullah Alsahli; Mohammed Nasser Alyemeni (Journal of Plant Growth Regulation, 2021)

Geological and Geomorphological Characteristics of Hingol National Park (HNP), Balochistan: a Geoheritage Candidate from Southern Pakistan - Muhammad Yaseen; Abbas Ali Naseem; Jawad Ahmad; Afrasiab Khan; Abdullah Khan; Muhammad Alamzeb; Adnan Ahmad; Usman Saeed; Arsalan Ahmad (Geoheritage, 2021)

Evaluation of sex steroid hormones and reproductive irregularities in diethyl phthalate-exposed premature mice: modulatory effect of raw honey against potential anomalies - Chaman Ara; Asmatullah; Faiza Yaseen; Shaukat Ali; Hafiz Abdullah Shakir; Muhammad Khan; Shagufta Andleeb; Nageena Ramzan (Environmental Science and Pollution Research, 2021)

Sources, chemistry, bioremediation and social aspects of arsenic-contaminated waters: a review - Syed Ejaz Hussain Mehdi; Rabia Amen; Awais Ali; Hirra Anjum; Abid Mahmood; Muhammad Mubashir; Ahmad Mukhtar; Sami Ullah; Abdullah G. Al-Sehemi; Muhammad Ibrahim; Mohd Shariq Khan; Muhammad Abdul Qyyum; et al. (Environmental Chemistry Letters, 2021)

Sulfate-Based Fertilizers Regulate Nutrient Uptake, Photosynthetic Gas Exchange, and Enzymatic Antioxidants to Increase Sunflower Growth and Yield Under Drought Stress - Bilal Ahamid Shafiq; Fahim Nawaz; Sadia Majeed; Muhammad Aurangzaib; Abdullah Al Mamun; Muhammad Ahsan; Khawaja Shafique Ahmad; Muhammad Asif Shehzad; Muqarrab Ali; Sarfraz Hashim; Tanveer ul Haq (Journal of Soil Science and Plant Nutrition, 2021)
The challenging impact of drought to agricultural productivity requires the adoption of mitigation strategies with a better understanding of underlying mechanisms responsible for drought tolerance. The present study aimed at investigating the effects of sulfur-based fertilizers on mitigation of drought stress in sunflower. Sulfate-containing fertilizers, viz., ammonium sulfate, zinc sulfate, magnesium sulfate, potassium sulfate, and gypsum, were initially evaluated at two different rates (10 and 20 mg kg −1 soil equivalent to 20 and 40 kg ha −1 , respectively) for nutrient uptake and growth-promoting traits in sunflower seedlings (cv. Hysun-33). The best performing fertilizer (gypsum) was then selected to evaluate the response of sunflower under drought stress imposed at flowering stage for three weeks (25–30% water holding capacity). Results indicated significant amelioration of drought stress with higher activity of photosynthetic apparatus, upregulation of antioxidative enzymes, and increased achene yield by gypsum application. In comparison to control, gypsum-treated plants (20 mg kg −1 soil) exhibited higher water status (32%), leaf photosynthetic rate (29%), transpiration rate (67%), and stomatal conductance (118%) under drought stress. The antioxidant enzyme activities of catalase, guaiacol peroxidase, and superoxide dismutase were also increased by 67%, 62%, and 126%, respectively, resulting in higher achene yield (19%) under water-deficit conditions. This study indicates that the application of sulfur-based fertilizers (gypsum) can be used to induce drought tolerance and obtain high sunflower yields under drought stress, and furthermore, it is a cost-effective strategy resulting in high benefit–cost ratio with respect to no gypsum application.

In Silico Mutagenesis-Based Remodelling of SARS-CoV-1 Peptide (ATLQAIAS) to Inhibit SARS-CoV-2: Structural-Dynamics and Free Energy Calculations - Abbas Khan; Shaheena Umbreen; Asma Hameed; Rida Fatima; Ujala Zahoor; Zainib Babar; Muhammad Waseem; Zahid Hussain; Muhammad Rizwan; Nasib Zaman; Shahid Ali; Muhammad Suleman; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Evaluation of Cadmium Chloride-Induced Toxicity in Chicks Via Hematological, Biochemical Parameters, and Cadmium Level in Tissues - Shaukat Ali; Saleha Bashir; Shumaila Mumtaz; Hafiz Abdullah Shakir; Chaman Ara; Farooq Ahmad; Hafiz Muhammad Tahir; Mehwish Faheem; Muhammad Irfan; Azeem Masih; Mazhar Ulhaq; Saiqa Andleeb (Biological Trace Element Research, 2021)

Chemiluminescent-microparticle-immunoassay-based detection and prevalence of human immunodeficiency virus infection in Islamabad, Pakistan - Misbahud Din; Faheem Anwar; Muhammad Ali; Muhammad Yousaf; Bilal Ahmad; Abdullah (Archives of Virology, 2021)

Fabrication of TiO2@ITO-grown nanocatalyst as efficient applicant for catalytic reduction of Eosin Y from aqueous media - Abdul Hameed Pato; Aamna Balouch; Farah Naz Talpur; Abdullah; Pirah Panah; Ali Muhammad Mahar; Muhammad Saqaf Jagirani; Sagar Kumar; Safia Sanam (Environmental Science and Pollution Research, 2021)

Lead contamination in shooting range soils and its phytoremediation in Pakistan: a greenhouse experiment - Amir Zeb Khan; Sardar Khan; Said Muhammad; Shams Ali Baig; Abdullah Khan; Muhammad Jamal Nasir; Madiha Azhar; Alia Naz (Arabian Journal of Geosciences, 2021)

Influence of Different Organic Manures and Their Combinations on Productivity and Quality of Bread Wheat - Nauman Ali; Muhammad Naeem Khan; Muhammad Saeed Ashraf; Sobia Ijaz; Hafiz Saeed-ur-Rehman; Muhammad Abdullah; Noor Ahmad; Hafiz Muhammad Akram; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2020)

Synthesis, Structure Study, First-Principles Investigations and Luminescence Properties of Europium and Terbium Complexes - Bakhat Ali; Helio A. Stefani; Muhammad Imran; Ahmad Irfan; Mohammed A. Assiri; Maria Claudia F. C. Felinto; Muhammad Khalid; Abdullah G. Al-Sehemi (Journal of Fluorescence, 2020)

Economic impact assessment of natural disaster with multi-criteria decision making for interdependent infrastructures - Muhammad Abdullah Khalid; Yousaf Ali (Environment, Development and Sustainability, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cardiac toxicity of heavy metals (cadmium and mercury) and pharmacological intervention by vitamin C in rabbits - Shaukat Ali; Zubia Awan; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Siddique Awan; Saima Sharif; Muhammad Irfan; Muhammad Adeeb Khan (Environmental Science and Pollution Research, 2020)

Dose and duration-dependent toxicological evaluation of lead acetate in chicks - Saeeda Hussain; Shaukat Ali; Shumaila Mumtaz; Hafiz Abdullah Shakir; Farooq Ahmad; Hafiz Muhammad Tahir; Mazhar Ulhaq; Muhammad Adeeb Khan; Muhammad Tariq Zahid (Environmental Science and Pollution Research, 2020)

Therapeutic role of garlic and vitamins C and E against toxicity induced by lead on various organs - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Samiara Mumtaz; Saiqa Andleeb (Environmental Science and Pollution Research, 2020)

Fabrication of Pt-Pd@ITO grown heterogeneous nanocatalyst as efficient remediator for toxic methyl parathion in aqueous media - Ali Muhammad Mahar; Aamna Balouch; Farah Naz Talpur; Abdullah; Pirah Panah; Raj Kumar; Ameet Kumar; Abdul Hameed Pato; Dadu Mal; Sagar Kumar; Akrajas Ali Umar (Environmental Science and Pollution Research, 2020)

Characteristically Insights, Artificial Neural Network (ANN), Equilibrium, and Kinetic Studies of Pb(II) Ion Adsorption on Rice Husks Treated with Nitric Acid - Sami Ullah; Mohammed Ali Assiri; Abdullah Ghodran Al-Sehemi; Mohamad Azmi Bustam; Muhammad Sagir; Firas Ayad Abdulkareem; Muhammad Rafi Raza; Muhammad Ayoub; Ahmad Irfan (International Journal of Environmental Research, 2020)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Different nitrogen and biochar sources’ application in an alkaline calcareous soil improved the maize yield and soil nitrogen retention - Muhammad Farooq Qayyum; Mehak Ameer Abdullah; Muhammad Rizwan; Ghulam Haider; Muhammad Arif Ali; Muhammad Zafar-ul-Hye; Muhammad Abid (Arabian Journal of Geosciences, 2019)

Green vehicle adoption behavior among low-income households: evidence from coastal Malaysia - Abdullah Al Mamun; Muhammad Mehedi Masud; Syed Ali Fazal; Rajennd Muniady (Environmental Science and Pollution Research, 2019)

Calcified cyanobacteria fossils from the leiolitic bioherm in the Furongian Changshan Formation, Datong (North China Platform) - Khalid Latif; Enzhao Xiao; Muhammad Riaz; Abdullah Ali Ali Hussein (Carbonates and Evaporites, 2019)

Toxicological effects of toxic metals (cadmium and mercury) on blood and the thyroid gland and pharmacological intervention by vitamin C in rabbits - Rida Khan; Shaukat Ali; Shumaila Mumtaz; Saiqa Andleeb; Mazhar Ulhaq; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Muhammad Adeeb Khan; Hafiz Abdullah Shakir (Environmental Science and Pollution Research, 2019)

Exploring of bioactive compounds in essential oil acquired from the stem and root derivatives of Hypericum triquetrifolium callus cultures - Nawroz Abdul-Razzak Tahir; Hoshyar Abdullah Azeez; Kadhm Abdullah Muhammad; Shewa Anwer Faqe; Dlshad Ali Omer (Natural Product Research, 2019)

Different ambient management intervention techniques and their effect on milk production and physiological parameters of lactating NiliRavi buffaloes during hot dry summer of subtropical region - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Rahman Ullah; Qurat ul Ain; Muhammad Sajid Hasni; Mahboob Ali; Abdul Rashid; Imran Qaisar; Ghazunfar Rashid; Rafi Uddin (Tropical Animal Health and Production, 2019)

The protective role of ascorbic acid in the hepatotoxicity of cadmium and mercury in rabbits - Shumaila Mumtaz; Shaukat Ali; Rida Khan; Saiqa Andleeb; Mazhar Ulhaq; Muhammad Adeeb Khan; Hafiz Abdullah Shakir (Environmental Science and Pollution Research, 2019)

Renal toxicity of heavy metals (cadmium and mercury) and their amelioration with ascorbic acid in rabbits - Shaukat Ali; Sidra Hussain; Rida Khan; Shumaila Mumtaz; Nasra Ashraf; Saiqa Andleeb; Hafiz Abdullah Shakir; Hafiz Muhammad Tahir; Muhammad Khalil Ahmad Khan; Mazhar Ulhaq (Environmental Science and Pollution Research, 2019)

Effect of ambient management interventions on the production and physiological performance of lactating Sahiwal cattle during hot dry summer - Mehtab Ahmad; Jalees Ahmed Bhatti; Muhammad Abdullah; Khalid Javed; Mehboob Ali; Ghazanfar Rashid; Rafi Uddin; Ali Hassan Badini; Mudassar Jehan (Tropical Animal Health and Production, 2018)

The dynamic relationship between structural change and CO2 emissions in Malaysia: a cointegrating approach - Wajahat Ali; Azrai Abdullah; Muhammad Azam (Environmental Science and Pollution Research, 2017)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Modelling the kinetics of hexavalent molybdenum (Mo6+) reduction by the Serratia sp. strain MIE2 in batch culture - Mohd Izuan Effendi Halmi; Siti Rozaimah Sheikh Abdullah; Wan Lutfi Wan Johari; Mohd Shukuri Muhammad Ali; Noor Azmi Shaharuddin; Ariff Khalid; Mohd Yunus Shukor (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

Random mutagenesis and media optimisation for hyperproduction of cellulase from Bacillus species using proximally analysed Saccharum spontaneum in submerged fermentation - Roheena Abdullah; Wajeeha Zafar; Muhammad Nadeem; Mehwish Iqtedar; Shagufta Naz; Quratulain Syed; Zahid Ali Butt (Natural Product Research, 2015)

Changes in extreme temperature and precipitation in the Arab region: long‐term trends and variability related to ENSO and NAO - M. G. Donat; T. C. Peterson; M. Brunet; A. D. King; M. Almazroui; R. K. Kolli; Djamel Boucherf; Anwar Yousuf Al‐Mulla; Abdourahman Youssouf Nour; Ahmed Attia Aly; Tamer Ali Ali Nada; Muhammad M. Semawi; et al. (International Journal of Climatology, 2014)
A workshop was held in Casablanca, Morocco, in March 2012, to enhance knowledge of climate extremes and their changes in the Arab region. This workshop initiated intensive data compilation activities of daily observational weather station data from the Arab region. After conducting careful control processes to ensure the quality and homogeneity of the data, climate indices for extreme temperatures and precipitation were calculated. This study examines the temporal changes in climate extremes in the Arab region with regard to long‐term trends and natural variability related to ENSO and NAO . We find consistent warming trends since the middle of the 20th Century across the region. This is evident in the increased frequencies of warm days and warm nights, higher extreme temperature values, fewer cold days and cold nights and shorter cold spell durations. The warming trends seem to be particularly strong since the early 1970s. Changes in precipitation are generally less consistent and characterised by a higher spatial and temporal variability; the trends are generally less significant. However, in the western part of the Arab region, there is a tendency towards wetter conditions. In contrast, in the eastern part, there are more drying trends, although, these are of low significance. We also find some relationships between climate extremes in the Arab region and certain prominent modes of variability, in particular El Niño‐Southern Oscillation ( ENSO ) and North Atlantic Oscillation ( NAO ). The relationships of the climate extremes with NAO are stronger, in general, than those with ENSO , and are particularly strong in the western part of the Arab region (closer to the Atlantic Ocean). The relationships with ENSO are found to be more significant towards the eastern part of the area of study. © 2013 Royal Meteorological Society

Expression and identification of folate-sensitive fragile sites in British Suffolk sheep (Ovis aries) - Ahmad Ali; Muhammad Abdullah; Masroor Ellahi Babar; Khalid Javed; Asif Nadeem (Journal of Genetics, 2008)